Pemanfaatan Limbah Paving Sebagai Alternatif Agregat Halus Terhadap Kuat Beton - Ulumuddin, Miftachul; Sasongko, Januar (Tolis Ilmiah : Jurnal Penelitian, 2025)
The demand for concrete as a primary construction material has increased significantly each year, leading to the excessive exploitation of natural sand and resulting in adverse environmental impacts. On the other hand, construction waste such as used paving blocks from road and sidewalk demolitions continues to accumulate without optimal reuse. This study aims to analyze the utilization of paving waste as a partial replacement for fine aggregate (sand) and its effect on the compressive strength of concrete, using paving waste variations of 5%, 10%, and 15%. The research method employed an experimental approach in the laboratory, with compressive strength tests conducted at 7 and 28 days in accordance with SNI 03-2834-2000. The test results show that concrete with 15% paving waste substitution achieved the highest compressive strength, reaching 20.70 MPa at 7 days and 27.98 MPa at 28 days, exceeding that of normal concrete (0%) which only reached 26.90 MPa. These findings indicate that paving waste has potential as an environmentally friendly alternative to fine aggregate, while also significantly enhancing the compressive strength of concrete.